Plant Movements as Concept Generators for the Development of Biomimetic Compliant Mechanisms. (12th May 2020) - Poppinga, Simon; Correa, David; Bruchmann, Bernd; Menges, Achim; Speck, Thomas
Synopsis: Plant movements are of increasing interest for biomimetic approaches where hinge-free compliant mechanisms (flexible structures) for applications, for example, in architecture, soft robotics, and medicine are developed. In this article, we first concisely summarize the knowledge on plant movement principles and show how the different modes of actuation, that is, the driving forces of motion, can be used in biomimetic approaches for the development of motile technical systems. We then emphasize on current developments and breakthroughs in the field, that is, the technical implementation of plant movement principles through additive manufacturing, the development of structures capable of tracking movements (tropisms), and the development of structures that can perform multiple movement steps. Regarding the additive manufacturing section, we present original results on the successful transfer of several plant movement principles into 3D printed hygroscopic shape-changing structures ("4D printing"). The resulting systems include edge growth-driven actuation (as known from the petals of the lily flower), bending scale-like structures with functional bilayer setups (inspired from pinecones), modular aperture architectures (as can be similarly seen in moss peristomes), snap-through elastic instability actuation (as known from Venus flytrap snap-traps), and origami-like curved-folding kinematic amplification (inspired by the carnivorous waterwheel plant). Our novel biomimetic compliant mechanisms highlight the feasibility of modern printing techniques for designing and developing versatile tailored motion responses for technical applications. We then focus on persisting challenges in the field, that is, how to speed-boost intrinsically slow hydraulically actuated structures and how to achieve functional resilience and robustness, before we propose the establishment of a motion design catalog in the conclusion.